The effects of metal surface geometry on the formation of uranium hydride. (September 2015) - Stitt, C.A.; Paraskevoulakos, C.; Harker, N.J.; Jones, C.P.; Scott, T.B.
Highlights: Surface topography influences uranium corrosion by hydrogen. High aspect ratio features were observed to nucleate hydride earliest. Reactivity is attributed to locally increased area to volume ratios and strain. Tests using smooth uranium surfaces may underestimate reactivity for real wastes. Abstract: The present work examines the effect of surface geometry on the reaction between hydrogen gas and uranium metal, forming uranium hydride (UH3 ), a pyrophoric compound of significance to the civil nuclear industry. Hydride formation was initiated on uranium samples that had been patterned with a focused ion beam instrument to form surface arrays of triangular prisms and pillars with differing apex angles. Post reaction analysis indicated preferential hydride formation at the apex of these features. Additionally, once hydride formation had commenced the observed growth rate on the prisms appeared to accelerate in comparison to the rate exhibited on the surrounding surface.